Salmonella enteritidis meningitis in an infant: Case report and literature review (2016)
Salmonella meningitis is an entity with relatively low incidence. In developed countries, it represents 1% of meningitis cases while in developing countries it may occur in up to 13%. Its treatment is difficult and there is no consensus about it.This article presents the case of an infant with a clinical picture consisting of coughing, runny nose, fever, tachycardia, tachypnea, hyporexia and hypoactivity, with cerebrospinal fluid (CSF) test compatible with bacterial meningitis and common germs culture positive for Salmonella spp, which was finally typified as Salmonella Enteritidis. The patient was mainly treated with meropenem showing favorable results.This case evidences the difficulty of antibiotic treatment for Salmonella spp meningitis, especially if it is taken into account that its management is based on case reports and expert recommendations due to the lack of randomized clinical trials.